Electroacupuncture treatment for sarcopenia: study protocol for a randomized controlled trial - Hao Li; Li Zhou; Xin Zhang; Qian Wen; Li Tian; Han Yang; Xirong Chen; Jinghan Yuan; Ning Li; Bingmei Zhu; Lin Zhang; Lingyun Lu (BMC Complementary Medicine and Therapies)
Abstract Introduction Sarcopenia is a disease primarily characterized by age-related loss of skeletal muscle mass, muscle strength, and/or decline in physical performance. Sarcopenia has an insidious onset which can cause functional impairment in the body and increase the risk of falls and disability in the elderly. It significantly increases the likelihood of fractures and mortality, severely impairing the quality of life and health of the elderly people. This disease poses a heavy burden on the healthcare system and society in our country, and currently, there are limited clinical intervention strategies for sarcopenia. This study aims to explore the clinical efficacy and safety of electroacupuncture in treating sarcopenia. Methods and analysis In this parallel-design, randomized, sham-controlled trial, a total of 168 elderly sarcopenia patients will be randomly assigned in a 1:1 ratio to receive either electroacupuncture (EA) or sham electroacupuncture (sEA) treatment. The acupuncture points used in the study are Hegu (LI4), Shousanli (LI10), Quchi (LI11), Binao (LI14), Futu (ST32), Liangqiu (ST34), Zusanli (ST36), and Jiexi (ST41). The participants will receive EA or sEA treatment three times per week for eight weeks. The primary outcome measure is the change in grip strength (GS) of the patients after the eight-week treatment. The secondary outcome measures include the changes in grip strength at the fourth and twentieth weeks, changes in appendicular skeletal muscle mass index (ASMI), the Short Physical Performance Battery (SPPB) score, the physical activity level (PAL) assessed by the International Physical Activity Questionnaire (IPAQ), assessment of expectations regarding the efficacy of acupuncture, patient subjective evaluation of efficacy, and evaluation of blinding efficacy of acupuncture. All statistical analyses will be conducted according to the intention-to-treat principle and as per the study protocol. Ethics and dissemination This study protocol was reviewed and approved by the Institutional Review Board of West China Hospital of Sichuan University (permission number: 2023 − 525). The participants will provide written informed consent to participate in this study. Trial registration Chinese Clinical Trial Registry ( http://www.chictr.org.cn ), Registration number: ChiCTR2300079294. Date of Registration: 2023-12-29.